A blockchain empowered and privacy preserving digital contact tracing platform. Issue 4 (July 2021) - Bandara, Eranga; Liang, Xueping; Foytik, Peter; Shetty, Sachin; Hall, Crissie; Bowden, Daniel; Ranasinghe, Nalin; De Zoysa, Kasun
Abstract: The spread of the COVID-19 virus continues to increase fatality rates and exhaust the capacity of healthcare providers. Efforts to prevent transmission of the virus among humans remains a high priority. The current efforts to quarantine involve social distancing, monitoring and tracking the infected patients. However, the spread of the virus is too rapid to be contained only by manual and inefficient human contact tracing activities. To address this challenge, we have developed Connect, a blockchain empowered digital contact tracing platform that can leverage information on positive cases and notify people in their immediate proximity which would thereby reduce the rate at which the infection could spread. This would particularly be effective if sufficient people use the platform and benefit from the targeted recommendations. The recommendations would be made in a privacy-preserving fashion and contain the spread of the virus without the need for an extended period of potential lockdown. Connect is an identity wallet platform which will keep user digital identities and user activity trace data on a blockchain platform using Self-Sovereign Identity(SSI) proofs. User activities include the places he/she has travelled, the country of origin he/she came from, travel and dispatch updates from the airport etc. With these activity trace records, Connect platform can easily identify suspected patients who may be infected with the COVID-19 virus and take precautions before spreading it. By storing digital identities and activity trace records on blockchain-based SSI platform, Connect addresses the common issues in centralized cloud-based storage platforms (e.g. lack of data immutability, lack of traceability). Highlights: Blockchain-empowered COVID-19 contact tracing platform has been introduced. Self-Sovereign Identity enabled mobile wallet has been introduced for contact tracing. Store user identity data and activity trace data on the blockchain using SSI proofs. SSI enabled storage addresses the common issues in cloud-based data storages.